Performance analysis of DSTATCOM employing various control algorithms. Issue 10 (3rd July 2017) - Mangaraj, Mrutyunjaya; Panda, Anup Kumar
Abstract : This research work introduces a new hybrid technique called quasi‐Newton back‐propagation based i cos ϕ control algorithm. Its structure is constructed on the concept of biological features like input neuron, target neuron, weight correction and more attractive due to its parallel computing, learning capability behaviour. Systematic step‐by‐step procedures are represented by mathematical equations in the MATLAB/Simulink platform. The fundamental weighted values of active and reactive power components of load currents are extracted using the proposed control technique to generate the reference source currents. Further, the reference source currents are used to generate switching pulses for voltage source converter (VSC) of the distributed static compensator (DSTATCOM). It is capable enough to perform several functions such as harmonic mitigation, power factor correction, load balancing and voltage regulation which further reduce the DC link voltage across the self‐supported capacitor of the VSC. Simulation and experimental validation demonstrates better performance of the suggested algorithm for operation of the DSTATCOM at different loading conditions.